Building Futuristic Data Centers: A Technical Deep Dive into Next-Generation Infrastructure - Srinivas Reddy Mosali (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive technical article explores the evolution and future trajectory of modern data center infrastructure, focusing on critical innovations across multiple domains. The article examines advanced energy systems, thermal management solutions, AI-driven automation, edge computing integration, and sophisticated security architectures that are reshaping data center operations. The article investigates how these technological advancements address escalating computational demands while maintaining sustainability and operational efficiency. Through detailed analysis of renewable energy integration, liquid cooling technologies, predictive analytics, and zero-trust security frameworks, the article demonstrates how next-generation data centers are achieving unprecedented levels of performance, reliability, and environmental sustainability. The article highlights the transformative impact of artificial intelligence and edge computing on infrastructure management, while emphasizing the critical role of integrated security measures in protecting distributed computing environments.